Data quality and arbovirus infection associated factors in pregnant and non-pregnant women of childbearing age in Brazil: A surveillance database analysis - do Nascimento Einloft, Ariadne Barbosa (One Health, 2021)
The dengue surveillance system in Brazil has registered changes in the disease's morbidity and mortality profile over successive epidemics. Vulnerable groups, such as pregnant women, have been particularly hard hit. This study assessed the quality of notifications of dengue cases among pregnant women and non-pregnant women of childbearing age in Brazil, in addition to discussing the factors associated with arbovirus infection in the group of pregnant women. We carried out a retrospective study of cases registered in the national arbovirus surveillance system between 2007 and 2017. The indicator for assessing quality was incompleteness. Logistic regression was used to analyze the association between dengue during pregnancy and sociodemographic, epidemiological, clinical, and laboratory variables. The incompleteness of the data in the notification form for dengue cases in women of childbearing age and pregnant women indicates a significant loss of information. Dengue was shown to be positively associated with Social Determinants of Health in both groups, with more severe effects among pregnant women. The incompleteness of the data can limit the quality of information from the notification system and the national assessment of the situation of the disease in women of childbearing age and pregnant women.